Evaluation of the toll-like receptor 6 Ser249Pro polymorphism in patients with asthma, atopic dermatitis and chronic obstructive pulmonary disease - Reinitz-Rademacher Karin; Rohde Gernot; Arinir Umut; Petrasch-Parwez Elisabeth; Parwez Qumar; Stemmler Susanne; Hoffjan Sabine; Schultze-Werninghaus Gerhard; Bufe Albrecht; Epplen Jörg T (BMC, 2005)
Abstract Background For allergic disorders, the increasing prevalence over the past decade has been attributed in part to the lack of microbial burden in developed countries ('hygiene hypothesis'). Variation in genes encoding toll-like receptors (TLRs) as the receptor system for the first innate immune response to microbial stimuli has been implicated in various inflammatory diseases. We evaluated here the role of a coding variation, Ser249Pro, in the TLR6 gene in the pathogenesis of asthma, atopic dermatitis (AD) and chronic obstructive pulmonary disease (COPD). Methods Genotyping of the Ser249Pro polymorphism in 68 unrelated adult patients and 132 unrelated children with asthma, 185 unrelated patients with COPD, 295 unrelated individuals with AD and 212 healthy control subjects was performed by restriction enzyme digestion. Results We found a weak association of the 249Ser allele with childhood asthma (p = 0.03). Yet, significance was lost after Bonferroni correction. No association was evident for AD or COPD. Conclusion Variation in TLR6 might play a role in the pathogenesis of childhood asthma.